Dynamic condicional quasicorrelation of the spot and future markets volatility - Müller, Fernanda Maria; Guerra, Renata Rojas; Souza, Adriano Mendonça (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
This paper aim is analyze the spillover information effect and dynamic conditional quasicorrelation volatility between spot and future market in Brazil, Germany and United States. In this purpose, it was estimated three bivariate GARCH-DCC models to Ibovespa, DAX, S&P500 and it is future contracts. The results indicate that de spot market is affected by the past informations from their own returns and their future market returns in all indices analyzed but DAX. About the volatility, the dynamic correlation volatility between spot and future market is very strong in all three cases.